Synthesis and characterisation of thermotropic liquid crystalline monomer : 4-methylphenyl 4-[2-(vinyloxy) ethoxy]benzoate - Zain, Mohamad Hussin (2000)
This thesis is primarily concerned with the synthesis of a new thermotropic liquid crystalline monomer and its characterisation by using elemental analysis, spectroscopic analysis and thermal analysis techniques. A new thermotropic liquid crystalline monomer, 4-methylphenyl 4-[2- (vinyloxy)ethoxy]benzoate (4MP4VEB) was synthesised by reacting 4- methylphenyl 4-hydroxybenzoate (4MP4HB) with 2-chloro-ethyl-vinyl ether in acetonic solution. The compound 4MP4HB as a mesogenic group was prepared from the reaction of p-hydroxybenzoic acid and p-cresol. The mesogenic group (4MP4HB) was also used to synthesise the other thermotropic liquid crystalline compound namely 4-methylphenyl 4-(3-hydroxypropoxy)benzoate (4MP4HPB) but without a monomer terminal.The attempted synthesis of other liquid crystalline monomer with a varying spacer length using a different approach only ended up with a precursor compound. Two precursors, namely 4-[4-(allyloxy)butoxy]benzoic acid (4ABBA) and 4-(allyloxy)benzoic acid (4ABA) were successfully synthesised for the preparation of thermotropic liquid crystals with an allyl group as a monomer terminal. The compound 4ABBA is a precursor that has a spacer linkage, while 4ABA is without a spacer linkage. The liquid crystalline compound and the synthesised precursors were characterised by elemental, spectroscopic and thermal analyses. The observation of thermal properties and liquid crystallinities under polarising microscope revealed that the compound 4MP4VEB exhibited the like-mosaic defect texture of nematic mesophase, while the compound 4MP4HPB exhibited the focal-conic texture of smectic A mesophase.